Histological response, pattern of tumor destruction and clinical outcome after neoadjuvant chemotherapy including bevacizumab or cetuximab in patients undergoing liver resection for colorectal liver metastases. Issue 7 (July 2015) - Stremitzer, S.; Stift, J.; Singh, J.; Starlinger, P.; Gruenberger, B.; Tamandl, D.; Gruenberger, T.
Abstract Aim We investigated whether the type of antibody [bevacizumab (bev) or cetuximab (cet)] added to neoadjuvant combination chemotherapy before curative liver resection was associated with histological response, the pattern of tumor destruction and clinical outcome in patients with colorectal liver metastases (CLM). Methods We investigated 138 patients with KRAS wild-type status (codon 12, 13 and 61) who received neoadjuvant chemotherapy including bev (n = 101) or cet (n = 37). The primary endpoint was histological response. Secondary endpoints were necrosis and fibrosis of metastases, radiological response, recurrence-free survival (RFS) and overall survival (OS). Results Histological response was not significantly different between the two groups (P = 0.19). A significantly higher fraction of patients in the bev group showed necrosis of the metastases of ≥50% (P < 0.001), while a higher fraction of patients in the cet group showed fibrosis of ≥40% (P = 0.030). Radiological response was not significantly different (P = 0.17). Median RFS was significantly shorter in the cet group in univariable analysis (HR 1.59 (95% CI 1.00, 2.51), P = 0.049), but this difference did not remain significant in multivariable analysis (P = 0.45). The 3-year OS rate was not significantly different (P = 0.73). Conclusions The addition of bevacizumab to combination chemotherapy showed more necrosis but less fibrosis of metastases compared to cetuximab and a trend towards higher histological and radiological response and longer RFS. Further investigations of biological tumor characteristics are required to individualize treatment combinations.